A review on advanced cooling techniques for photovoltaic panel. (2022) - Panda, Sampurna; Gupta, Manoj; Panda, Babita; Jena, Chitralekha; Nanda, Lipika; Pradhan, Arjyadhara; Malvi, C.S.
Abstract: Despite generally low efficiency, photovoltaic systems are frequently used. When the P.V. module heats up, its output decreases. This bump is directly related to the energy absorbed by the panel and is then transformed into heat and results in lower panel output, energy efficiency, performance, and the life of the panel. To avoid PV panel overheating and to keep panel temperatures low, cooling techniques can be utilized. This paper describes new advanced cooling methods along with the upcoming research trends. In order to meet the needs of experts who are devising to conduct, improve or develop any cooling techniques for modules, several characteristics and capacities associated to cooling are explained and presented.